2017
DOI: 10.1016/j.ajog.2016.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix regenerative graft attenuates the negative impact of polypropylene prolapse mesh on vagina in rhesus macaque

Abstract: BACKGROUND The use of wide pore lightweight polypropylene mesh to improve anatomical outcomes in the surgical repair of prolapse has been hampered by mesh complications. One of the prototype prolapse meshes has been found to negatively impact the vagina by inducing a decrease in smooth muscle volume and contractility and the degradation of key structural proteins (collagen and elastin), resulting in vaginal degeneration. Recently, bioscaffolds derived from extracellular matrix have been used to mediate tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Some investigators are looking for novel graft materials derived from the extracellular matrix that can promote site-specific functional tissue remodeling without the risk of erosion. 22 Until these novel pathways of prevention and treatment reach patient application, surgeons managing POP should understand the array of options available, and be able to guide their patients' decision-making with the available evidence on outcomes and risks.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators are looking for novel graft materials derived from the extracellular matrix that can promote site-specific functional tissue remodeling without the risk of erosion. 22 Until these novel pathways of prevention and treatment reach patient application, surgeons managing POP should understand the array of options available, and be able to guide their patients' decision-making with the available evidence on outcomes and risks.…”
Section: Discussionmentioning
confidence: 99%
“…Even a study using a macaques model for the investigation of extracellular matrix regenerative graft reported that regenerative extracellular matrix graft attenuated the negative impact of polypropylene on the vagina [47]. However, despite promising, mainly comparative studies in animals no randomized trial in humans has been initiated so far to compare any of those coating strategies to non-coated meshes.…”
Section: Discussionmentioning
confidence: 99%
“…This animal model has been also used to study the host response to implanted material. A reduced inflammatory response was reported following the implantation of an ECM graft into the macaque vagina compared to polypropylene mesh [113]. However, MSC-loaded biomaterial has not yet been implanted and studied in the macaque model.…”
Section: Influence Of Mesenchymal Stem Cell-based Tissue Engineered Cmentioning
confidence: 99%